Improving the Quality of Teacher Learning Using Multimedia Through Workshop Activities in Schools - Jaafar, Azhar; Murniyati, Murniyati; Kurniawan, Gilang; Darwati, Darwati; Radila, Gustina (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
This research aims to improve the quality of teacher learning through the use of multimedia by implementing workshop activities in the school environment. Modern education demands the use of technology in the teaching and learning process, and multimedia is an effective tool for improving the quality of learning. Workshops are considered a training method that can provide teachers with new knowledge and skills in using multimedia effectively. The research method used is Classroom Action Research with a cycle of planning, implementation, observation, and reflection. Research participants consisted of teachers at schools who were willing to take part in workshop activities. Data was collected through observation, interviews, and assessment of learning outcomes. The research results show a significant increase in teachers' ability to use multimedia in learning. The workshop provided new insights and increased teachers' confidence in integrating multimedia technology into their teaching. In addition, increased student engagement and motivation were also seen during the implementation of multimedia. Thus, this research presents recommendations for involving regular workshop activities as a sustainable strategy for improving the quality of teacher learning by utilizing multimedia in the school environment. The conclusions of this research provide a positive picture of the role of workshops in supporting the development of teachers' multimedia skills to achieve more innovative and interactive learning in the era of digital education.